2023
DOI: 10.1177/03635465231158385
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Repair Outcome in 3829 Patients With a Minimum Follow-up From 2 Years Up to 5 Years: A Meta-analysis on the Overall Failure Rate and Factors Influencing Failure

Abstract: Background: The importance of meniscal repair is widely accepted because of the association of loss of meniscal tissue with the development of early-onset knee arthritis. Many factors influencing the results of meniscal repair have been reported, but results remain controversial. Purpose: This meta-analysis determines the pooled meniscal repair failure rate of studies with a minimum follow-up of 2 years up to 5 years, with a mean follow-up of 43 months. Moreover, selected failure-influencing factors are analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…The overall failure rate was 15.5% (49/316) (range 0-33.3%) across the 13 studies [10]. Three studies [16,17,23] comparing failure rates between patients above and below the age of 40 years demonstrated a slight increase in failure rate in those over 40 compared to those under 40: 10% (5/50) vs. 6% 8(8/137) (OR 1.79, 95% CI 0.63-5.56, p = 0.34). The failure rate in knees that were known to be ACL-deficient was 13% (6/46 knees).…”
Section: Failure Ratesmentioning
confidence: 98%
See 1 more Smart Citation
“…The overall failure rate was 15.5% (49/316) (range 0-33.3%) across the 13 studies [10]. Three studies [16,17,23] comparing failure rates between patients above and below the age of 40 years demonstrated a slight increase in failure rate in those over 40 compared to those under 40: 10% (5/50) vs. 6% 8(8/137) (OR 1.79, 95% CI 0.63-5.56, p = 0.34). The failure rate in knees that were known to be ACL-deficient was 13% (6/46 knees).…”
Section: Failure Ratesmentioning
confidence: 98%
“…Where the operative techniques were reported, 63 meniscal repairs used an all-inside technique, 130 used inside-out, and 4 used an outsidein technique. In all-inside meniscus repairs, six studies reported the use of a Fast-Fix© system (Smith & Nephew, Andover, MA, USA) [10][11][12]14,22,23], one study reported the used of Biofix Arrow Fixation© [17], one study reported the use of a VIPER© repair system (Arthrex, Naples, FL, USA) [17], and one study reported the use of a Zone Specific II Meniscal Repair System (Linvatec, Largo, FL, USA) [12]. In studies where meniscus repair was performed using the inside-out technique, a Juggerstitch© Meniscal Repair Device and fast-fix system (Smith & Nephew, Andover, MA, USA) were utilized [10,20].…”
Section: Repair Techniquementioning
confidence: 99%
“…Years or decades may be needed before these failures produce enough symptoms to distinguish them from cases that healed anatomically. In the shorter term, expensive magnetic resonance imaging (MRI) or second-look arthroscopy, which may not be acceptable to every patient or institutional ethics committee, may be needed to identify these “silent failures.” 20…”
mentioning
confidence: 99%
“…Because reoperation is easiest to identify unequivocally, secondary meniscectomy or subsequent arthroplasty is often used to define failure of meniscal surgery. 7,9,17,23 Symptoms of pain, swelling, catching, or locking may be recorded if patients are interviewed and examined, 1,20 which is often not the case. A meniscal repair that fails to heal or a transplant that extrudes from the joint has probably lost much of its intended function but may not cause symptoms sufficient to warrant an additional procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation